Propagation of privileged waves in longitudinally inhomogeneous medium with linear birefringence and dichroism - Koev, M.S.; Kolomiets, I.S.; Savenkov, S.N.; Oberemok, Ye.A.; Skoblya, Yu.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Anisotropic properties of longitudinally inhomogeneous medium with linear
birefringence and dichroism were considered. Differential Jones matrix model for this
class of media was obtained. The equation for the polarization complex variable that
describes the evolution of polarization state in this class of media was found. Partial
solutions describing evolution of the privileged polarization states were obtained. The
features of privileged polarization states and the conditions of their existence in this class
of media were analyzed.